2009
DOI: 10.4260/bjft2009800900016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and free radical scavenging activity of Apis mellifera bee pollen from Southern Brazil

Abstract: Bee pollen is an agglomerate of pollen grains from various botanical sources, which are collected by the bees and mixed with nectar and secretion from the hypopharyngeal glands such as β-glycosidase enzymes. Bee pollen has a complex chemical composition constituted of carbohydrates, proteins, aminoacids, vitamins and minerals, and is considered a good nutritional source, beneficial to health, particularly because of the presence of phenolic compounds with antioxidant activity. Therefore, the aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
79
6
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 34 publications
23
79
6
7
Order By: Relevance
“…The percentage of crude fiber of pollen collected by the two stingless bee species (Table 1) was relatively high when compared to the values (mean: 3.4%; range 2,2-4,9%) reported by CARPES et al (2009) in pollen collected by A. mellifera from the Southern region of Brazil. However, the values reported for crude fiber in the present study were closer to those found by BELL et al (1983) in bee pollen from varieties of eucalyptus in Australia (6.9-15.6%).…”
Section: Crude Fibersmentioning
confidence: 88%
“…The percentage of crude fiber of pollen collected by the two stingless bee species (Table 1) was relatively high when compared to the values (mean: 3.4%; range 2,2-4,9%) reported by CARPES et al (2009) in pollen collected by A. mellifera from the Southern region of Brazil. However, the values reported for crude fiber in the present study were closer to those found by BELL et al (1983) in bee pollen from varieties of eucalyptus in Australia (6.9-15.6%).…”
Section: Crude Fibersmentioning
confidence: 88%
“…The chemical composition of bee-pollen showed an average of 7.40% moisture, 20.00% protein, 6.00% lipids, and 2.20% ash (Almeida-Muradian et al, 2005). Different values (4.20, 20.50, 4.90, and 2.90%, respectively) of Brazilian bee-pollen were found by Carpes et al (2009). The chemical composition of bee-pollen is known to vary according to the plant species from which the pollen was collected (Szczęsna et al, 2002;2006a;Morgano et al, 2012), the geographic origin (Serra Bonvehi and Escola Jorda, 1997;Carpes et al, 2009;Martins et al, 2011;Morgano et al, 2012), the season (Szczęsna et al, 2002;Morgano et al, 2012), and the storage and storage method (Human and Nicolson, 2006;Siuda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Honeybee-collected pollen provides a rich source of easily digestible protein (Crailsheim et al, 1992;Campos et al, 1996;Serra Bonvehi and Escola Jorda, 1997;Szczęsna, 2006a;b). In addition to proteins, pollen also contains carbohydrates, fats and minerals (Orzáez Villanueva et al, 2002;Szczęsna et al, 2002;Almeida-Muradian et al, 2005;Human and Nicolson, 2006;Szczęsna, 2006a;2007;Campos et al, 2008;Carpes et al, 2009;Martins et al, 2011;Morgano et al, 2012). The chemical composition of bee-pollen showed an average of 7.40% moisture, 20.00% protein, 6.00% lipids, and 2.20% ash (Almeida-Muradian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CARPES et al (2009), ao determinar a composição química do pólen coletado pela Apis mellifera africanizada, obtiveram a média de proteína de 20,47%.…”
Section: Resultsunclassified